2017
DOI: 10.28945/3705
|View full text |Cite
|
Sign up to set email alerts
|

Secure E-Examination Systems Compared: Case Studies from Two Countries

Abstract: Aim/Purpose: Electronic examinations have some inherent problems. Students have expressed negative opinions about electronic examinations (e-examinations) due to a fear of, or unfamiliarity with, the technology of assessment, and a lack of knowledge about the methods of e-examinations. Background: Electronic examinations are now a viable alternative method of assessing student learning. They provide freedom of choice, in terms of the location of the examination, and can provide immediate feedback; students a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
0
18
1
Order By: Relevance
“…The development of digitalized examination pilot studies and case studies are becoming an expected norm with universities developing responses to a growing online curriculum offering (e.g. Al-Hakeem & Abdulrahman, 2017 ; Alzu'bi, 2015 ; Anderson et al, 2005 ; Fluck et al, 2009 ; Fluck et al, 2017 ; Fluck, 2019 ; Seow & Soong, 2014 ; Sindre & Vegendla, 2015 ; Steel et al, 2019 ; Wibowo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The development of digitalized examination pilot studies and case studies are becoming an expected norm with universities developing responses to a growing online curriculum offering (e.g. Al-Hakeem & Abdulrahman, 2017 ; Alzu'bi, 2015 ; Anderson et al, 2005 ; Fluck et al, 2009 ; Fluck et al, 2017 ; Fluck, 2019 ; Seow & Soong, 2014 ; Sindre & Vegendla, 2015 ; Steel et al, 2019 ; Wibowo et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results of a survey conducted in the literature [6,7,8], today's students prefer online exams to paper exams (68.75%). Among the reasons given for preference is the increased speed and ease of editing responses, with one study showing that two -thirds (67%) of students reported a positive experience of taking online exams [9].…”
Section: The Attitude Of Students Towards Online Learning Formatmentioning
confidence: 99%
“…Students believe that online exams allow for more reliable assessment, with 78% of students reporting consistency between the online environment and their future real-world environment [9].…”
Section: The Attitude Of Students Towards Online Learning Formatmentioning
confidence: 99%
See 1 more Smart Citation
“…At the end of the exam the results are submitted directly to the database to be processed and saved [10]. Results can be compared with paper examination results that evaluated by the teacher and providing a high degree of security [11][12][13], The E-exam reduces the time for writing questions, correcting papers, and printing the results [14]. It provides clear instructions to answer the questions in exams which reduces the ambiguous questions that weaken the tests' reliability.…”
Section: Introductionmentioning
confidence: 99%